Anticytokine therapy with interleukin-17 in patients with moderate and severe psoriasis - Julia S. Kovaleva; Igor V. Kazantsev; Annetta A. Aibazova; Ekaterina O. Ovchinnikova; Anastasia A. Garina; Anastasia P. Shabaldina (State Scientific Center of Dermatovenereology and Cosmetology, 2024)
Clinical observations of three patients aged 26, 43 and 37 years with severe psoriasis and psoriatic arthritis are presented. Clinical examples show the experience of effective treatment of patients with psoriasis and psoriatic arthritis using anti-cytokine therapy with an interleukin-17 inhibitor, initiated when the disease progresses. The clinical picture of the presented observations was characterized by an aggressive course of the skin and articular process, torpidity to basic therapy, despite the young age of the patients. It has been shown that the early termination of the progression of the inflammatory process in psoriasis with the use of genetically engineered biological therapy with secukinumab leads to a decrease in symptoms, both on the part of the skin and manifestations of the disease on the part of the musculoskeletal system. The high efficacy and safety of the drug allow complete control of the disease and improve the quality of life in patients suffering from severe forms of dermatosis.